Occupational Closure and Wage Inequality: How Occupational Closure Effects Vary Between Workers - Johannes Giesecke; Martin Groß; Stefan Stuth (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
Occupational closure continuously establishes, contests, or reinforces institutional boundaries around occupations. Occupational closure thereby interferes with wage-setting processes in the labor market. Recent research shows a~substantial impact of occupational closure on wage determination processes in Germany. However, research on occupational closure is based on the assumption that all incumbents of an occupation benefit in the same way. We challenge this assumption by showing that occupational closure works differently for different workers. Using the 2006 sample of the German Structure of Earnings Survey, we distinguish nine worker profiles (three educational groups crossed with three career stages). For each of these profiles we investigate the effects of five closure sources (credentialism, standardization, licensure, representation by occupational associations, and unionization) on the expected mean wages of occupations, employing a~two-step multilevel regression model. Our results show that occupational closure does indeed differ between workers. We can show that closure plays out differently throughout employees' careers. For example, representation through occupational associations pays off the most as employees' careers advance. Closure sources are unequally distributed across occupations and benefit employees with tertiary degrees more than employees with vocational qualifications. Credentialism also yields the largest advantages for workers with tertiary degrees regarding wage rents. However, our analyses also point to complex interactions between credentialism and standardization, demanding further research, to investigate the interplay between individual worker characteristics and the various sources of occupational closure.
Keywords: 300; Occupational closure; Wage determination; Occupational career; Heterogeneous effects; Multilevel model; Berufliche Schließung; Arbeitseinkommen; Berufliche Karriere; Heterogene Effekte; Multilevelmodell